Identitas Lokal Masyarakat Etnik Panaragan - Yusuf Adam Hilman; Ekapti Wahjuni Dwijayanti; Khoirurrosyidin Khoirrurosyidin (Sospol : Jurnal Sosial Politik, 2020)
People of Ponorogo is believed to have mystical or supernatural abilities. Public perception understands the character of Ponorogonese as Warok who tends to speak assertive, open, and rude. Warok is the one of antagonist theatrical drama player of Reyog. Negative stigma arises based on the lack of public understanding of the history of Paragan culture. Panaragan's identity actually has noble cultural values. This paper aims to identify Panaragan ethnic identity, in greater depth based on its distribution of settlement, art performance, patterns of interaction, language, and the practice of visualizing identity and characteristics in public spaces. The descriptive qualitative method was applied through data collection from the results of literature studies and observations. Data analysis through triangulation techniques was sourced from literature review of journals, books, and documentation obtained in the field. Panaragan ethnic local identity is influenced by, 1) Reyog performance art that popularized the figure of Warok as a powerful and influential person. In Javanese society, the term Warok is identical to Wewarah, which is understood as someone who is able to teach others about a good life. In the understanding of Islam, wara’ is a social status for those who take the Sufi path. Unfortunately, during the era of colonialism, the figure of Warok was constructed into an image that was used to frightening people and maintain the ruler authority; 2) The Panaragan dialect 'Warokan' is spoken in a straightforward and assertive manner with high intonation which is the influence of art performance Reyog's diction and language style. On the other hand, cultural construction through visual arts symbols and Panaragan cultural performances represent the character of the Ponorogo indigenous people who are persistent, independent, brave, and adventurous.